Natural fermion hierarchies from random Yukawa couplings - Gero von Gersdorff (Journal of High Energy Physics, 2017)
Abstract The Standard Model of particle physics requires Yukawa matrices with eigenvalues that differ by orders of magnitude. We propose a novel way to explain this fact without any small or large parameters. The mechanism is based on the observation that products of matrices of random order-one numbers have hierarchical spectra. The same mechanism can easily account for the hierarchical structure of the quark mixing matrix.